Fashion to Dysfunction: The Role of Plastic Pollution in Interconnected Systems of the Environment and Human Health - Adelaide Parks Lovett; Leslie Browning-Samoni; Charles Freeman (Textiles)
The rapid production and disposal of synthetic textiles, driven by fast fashion and overconsumption, contribute significantly to environmental pollution and human health risks. Functional finishes often contain toxic substances that leach into aquatic systems. Laundering and abrasion release microplastic fibers (MPFs), commonly called microplastics, and anthropogenic microfibers (MFs) which degrade into nanoplastics (NPs) through mechanical stress, heat, and UV radiation. These particles bypass wastewater treatment and accumulate in human organs, including the liver, lungs, and brain. This review highlights the limitations of current waste management systems, the role of textile design in particle release, and the need for further research on airborne emissions and environmental interactions. Mitigating textile-derived plastic pollution will require biodegradable finishes, pre-consumer filtration systems, and circular consumption models supported by interdisciplinary collaboration.